A relação entre os aspectos psicológicos e as doenças hipertensivas gestacionais: uma revisão sistemática - Magno, Patricia Lomonaco (2011)
Gestational hypertensive disorders are the main cause of maternal and fetus mortality in Brazil and in the world. Studies addressing the psychological dimensions of pregnancy-induced hypertension (PIH) are still scarce, despite their increase in the last few years. Objective: This study performed a systematic review of the literature addressing the psychological aspects of hypertensive pregnant women and PIH, in order to investigate if a relationship can be established between variables and their significance. Method: To comprise the bibliographic review, twenty-four articles were located in the Scielo, Pubmed and Web of Science databases. The key words in Portuguese researched were: hipertensão , hipertensão gestacional , gestacional , pré-eclampsia , eclampsia , síndrome HELLP , gravidez , gestante , gestação de alto risco , gestação de risco , repouso hospitalar , aspectos psicológicos , psicossomática , ansiedade , estresse and Kahhale . In English, the key words used to perform the research were: hypertension , preeclampsia , pre eclampsia , eclampsia , HELLP syndrome , hospitalization , high risk pregnancy , pregnancy , pregnant , psycological , psycosocial , psychosomatics , pregnancy induced hypertension , anxiety , stress , depression and motherhood and diseases . To serve as a basis for the theoretical concepts presented in this study, specific chapters dealing with PIH, psychosomatics and psychoneuroimmunology and psychological aspects of pregnant women were drafted. The articles selected were translated, analyzed and their results were compared. Analysis and Discussion: Although the root cause of this disorder is still unknown, the studies that comprise this systematic review indicate that there is strong evidence suggesting that psychological aspects can influence in the appearance and development of this diagnosis, especially stress (distress). Possible mechanisms for coping with stressful situations and results of this diagnosis are also examined by the relevant literature, with an aim to understand the functioning of distress. Conclusion: Although the studies presented indicate that psychological aspects are related to PIH, additional studies are recommended to better identify and understand the relationship between the different variables and their actual consequences. Psychotherapeutic treatment, as well as psychosocial support and the formation of a good relationship with the medical staff, can help women who have limited or ineffective mechanisms, in situations of stress